University living learning lab - co-creation for sustainability - Zen, Irina Safitri (2019)
Analyse University's living learning lab framework which has function as a demonstration site for sustainable development goals, SDGs by integrating teaching learning, research, campus operation and community engagement. The presentation is part of roundtable discussion 'Education 2030 agenda for quality higher education', which deliberate on matters pertaining to “Higher Education and Sustainable Development Goals (SDGs)” in the context of the Commonwealth in general and Malaysia in particular.